Formulation and Evaluation of Amikacin Sulfate Loaded Dextran Nanoparticles against Human Pathogenic Bacteria - Rahamat Unissa Syed; Sivakumar S. Moni; Muhammad Nawaz; Mohammed Khaled Bin Break; Nasrin E. Khalifa; Siddig Ibrahim Abdelwahab; Reham Meshal Alharbi; Raghad Huraid Alfaisal; Bayan Naif Al Basher; Entsar Mohammed Alhaidan (MDPI AG, 2023)
Amikacin sulfate-loaded dextran sulfate sodium nanoparticles were formulated, lyophilized (LADNP), and then analyzed. The LADNP had a −20.9 ± 8.35 mV zeta potential, PDI of 0.256, and % PDI of 67.7. The zeta average nano size of LADNP was 317.9 z. d.nm, while the dimension of an individual particle was 259.3 ± 73.52 nm, and nanoparticle conductivity in colloidal solution was 2.36 mS/cm. LADNP has distinct endothermic peaks at temperatures at 165.77 °C, according to differential scanning calorimetry (DSC). The thermogravimetric analysis (TGA) showed the weight loss of LADNP, which was observed as 95% at 210.78 °C. XRD investigation on LADNP exhibited distinct peaks at 2θ as 9.6°, 10.4°, 11.4°, 18.9°, 20.3°, 24.4°, 28.2°, 33.2°, 38.9°, and 40.4° confirming crystalline structure. The amikacin release kinetics from LADNP revealed zero order kinetics with a linear release showed zero order kinetics with 37% of drug release in 7 h and had an R2 value of 0.99. The antibacterial effect of LADNP showed broad-spectrum activity against tested human pathogenic bacteria. The preset study demonstrated that LADNP is a promising antibacterial agent.